2008
DOI: 10.1097/01.nna.0000323957.44791.b9
|View full text |Cite
|
Sign up to set email alerts
|

Job and Industry Turnover for Registered and Licensed Vocational Nurses

Abstract: Most studies of nurse turnover focus on job turnover, which could reflect nurse advancement and thus not be detrimental to the workforce. The authors discuss findings from a study that involved 2 cohorts of graduates from registered nursing and licensed vocational nursing community college programs in California. The duration of employment in the healthcare industry, as well as with specific employers, is tracked, lending a more thorough analysis of nursing job and industry turnover than found in other studies. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Nursing turnover rates range from 15% to 36% and the average separation rate for all healthcare employees is 29.6%. (Spetz, Rickles, Chapman, & Ong, 2008) Additionally temporary staff account for about 5% of all nursing care hours. (Jones, 2008) Temporary staff may not be knowledgeable of the devices used in each facility.…”
Section: Resultsmentioning
confidence: 99%
“…Nursing turnover rates range from 15% to 36% and the average separation rate for all healthcare employees is 29.6%. (Spetz, Rickles, Chapman, & Ong, 2008) Additionally temporary staff account for about 5% of all nursing care hours. (Jones, 2008) Temporary staff may not be knowledgeable of the devices used in each facility.…”
Section: Resultsmentioning
confidence: 99%
“…One telling study (Spetz, Rickles, Chapman, & Ong, 2008) suggested that nurses may not burnout to nursing but rather to particular nursing settings, supervisors, or jobs. The study found that 76% of the nurses who were tracked remained in the healthcare/nursing industry, although they left their healthcare employers.…”
Section: Statement Of the Problemmentioning
confidence: 97%
“…Antecedents to voluntary turnover intentions include burnout, work stress, lack of collaboration among health care professionals, ineffective management, job dissatisfaction, and demographic factors such as younger age, higher education, and having children in the household (Coomber & Barriball, 2007; Hayes et al; Spetz, Rickles, Chapman, & Ong, 2008). …”
Section: Literature Reviewmentioning
confidence: 99%